Implementasi Metode Analytical Hierarchy Process (AHP) Pada Sistem Pendukung Keputusan Pemilihan Security Terbaik Di PT. Adimulio Palmo - Junaidi Surya; Novhirtamely Kahar; Rika Angelina; Teuku Djauhari (LP2M Universitas Nurdin Hamzah, 2026)
This study discusses the design of a decision support system for selecting the best security guard at PT Adimulio Palmo Lestari using the Analytical Hierarchy Process (AHP) method. The purpose of this study is to assist the company in determining the most suitable security guard based on several criteria, namely discipline, ethics, achievement, experience, and attendance. The calculation process is carried out by comparing each criterion in pairs to obtain priority weights. The results of the study indicate that the decision support system based on the AHP method is able to provide objective and consistent security rankings. Thus, this system is expected to support faster, more precise, transparent, and accurate decision making in the process of selecting the best security guard.